Academic research contributions from Ibero-American countries to general knowledge, engineering, and computer science up to 2023 and COVID impact (2024)
Although commonly, competitive intelligence analysis is applied to companies, where new investments and operation expenditures are considered along with changes in the market, competitive intelligence can be applied to different countries' academic research production, which impacts science, technology and innovation making a difference in their competitiveness. This work shows the academic research production for all areas of knowledge, and also specifically for engineering and computer science, from all the Ibero-American countries, based on the SCOPUS database from 2001 to 2023. The results show that based on the volume of their academic production, for an affordable analysis, the Ibero-American countries can be classified into three groups, considering an order of magnitude difference for each group. The leading group is composed of countries producing between 200,000 and about 2 million documents, the second group of countries producing between 20,000 and 200,000 documents, and the third group of countries producing between 2,000 and 20,000 documents. The COVID pandemic impacted all the countries which showed a decrease in annual production over the last two years. The results also show the priority areas of knowledge that these countries invest in and the main countries that they collaborate with. The behavior of production for engineering and computer science is like that of general production, but there are some specific internal factors for specific countries such as in the case of Brazil, the country in which production fell most dramatically, followed by Spain and Colombia. On the other hand, Peru and Ecuador show a high interest in engineering and computer science. This work offers a high value decision-making tool to leaders in academic research, the principals of research driven institutions and investors from industry in Ibero-America. The academic production is related to the size of the GDP and the percentage of the GDP invested by a country in research development and innovation.